Evaluation of Sugar Factory Privatization Practices in Turkey: The Case of Kayseri Sugar Factory- Turhal - , Gizem Kayalı, Dilek Bostan Budak, Merve Ayyıldız (Archives of Current Research International, 2024)
The primary aim of this research is to assess the privatization process of sugar factories in Turkey, with a particular focus on the perspective of sugar beet producers. The study specifically examines sugar beet producers associated with the Turhal Sugar Factory. The distribution of the sample size across the production regions was determined by considering the number of producers in each region. The nine production regions in question exhibit similar characteristics in terms of geography and general agricultural features. The sample size was determined to be 150, with a 90 %confidence interval and 5% margin of error from the mean. The findings indicate that 43,3% of the farms experienced a reduction in sugar beet cultivation areas following privatization, with this decline being more significant among small scale farms. This suggests that small farms require additional support to maintain their sustainability. When compared to Türkşeker, producers generally expressed satisfaction with the services provided by the factory post-privatization. However, concerns about the factory’s future inactivity grow as farm size increases. While many studies have demonstrated that privatized factories tend to be more efficient and effective, this research also highlights the producers’ apprehensions regarding the operations of private factories. Thus, it is crucial to address these concerns with privatization policies and implement measures to ensure the continued operations of these factories. Another significant issue is the pricing of pulp, a vital by-product for livestock farming. Therefore, then setting pulp prices, consideration should be given to both the market price and the region’s livestock potential.